Model Analisis Defisiensi Struktur dan Sistem Organisasi Proyek Sebagai Kontributor Kecelakaan Konstruksi dalam Pembangunan Infrastruktur - Febrian, Atharika Yosa; Suraji, Akhmad; Hidayat, Benny (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The aim of this research is to identify and determine significant factors from structural deficiencies and project organizational systems as contributors to construction accidents which can be used as tools/instruments for construction safety audits. This quantitative research was processed using the Bayesian Belief Networks (BBN) method and modeled using the free download Hugin Lite 9.1 software. Based on the research results, the factor that contributes most significantly based on prediction simulations developed using the Bayesian Belief Networks model using Hugin Lite 9.1 free download software is a deficiency in the project organization system from the contractor's side with the largest 3 (three) probability values, namely risk identification and assessment by contractors who do not adequate 82.52%, construction implementation procedures incorrect 75.62% and lack of knowledge related to construction safety 70%.